MECHANICAL BEHAVIORS OF BANANA AND SISAL HYBRID COMPOSITES REINFORCED USING OF VARIOUS PARAMETER - Patel, Hemant; Parkhe, Ashish; Shrama, P.K. (International Journal of Engineering Technologies and Management Research, 2016)
To develop and commercialize materials containing vegetal fibers has grown in order to reduce environmental impact. Large amounts of lignocellulosic materials are generated around the world from several human activities and some process. Development of the Polymer Composites with natural fibers and fillers such as a sustainable alternative material for some applications, particularly in aerospace applications and automobile applications are being investigated. Natural fiber composites such as sisal, jute, hemp and coir polymer composites appear more attractive due to their higher specific strength, lightweight and biodegradability and low cost.